Swept-source optical coherence tomography in ocular surface diseases: anterior segment analysis repeatability and its limits - Recchioni, Alberto; Venkataraman, Abinaya Priya; Rauz, Saaeha; Domínguez-Vicent, Alberto (Frontiers in Medicine, 2024)
This study aims to evaluate the repeatability of anterior segment optical coherence tomography (AS-OCT) in diverse ocular surface disorder (OSD) cohorts, exploring various anterior segment parameters and their accuracy in different disease groups.A total of 239 participants across six distinct OSD groups and healthy controls underwent nonmydriatic AS-OCT imaging using the Tomey CASIA 2 device. Anterior segment parameters including anterior chamber depth, width, angle metrics, corneal thickness, keratometry, lens vault, and others were meticulously assessed. Statistical analyses determined repeatability limits and coefficients of variation for each parameter within the different OSD cohorts.Repeatability for anterior chamber and corneal parameters remained consistent across all OSD groups, indicating minimal impact of ocular surface disease on accuracy. The coefficient of variation (CoV) for the trabecular iris-space area was about 20% for all cohorts. Ocular surface inflammation emerged as a key factor in dry eye, affecting immune-mediated and non-immune conditions alongside age-related ocular surface changes. While anterior chamber depth measurements showed variations, particularly in immune (CoV=2.5%) and non-immune (CoV=3.8%) OSD groups, parameters like anterior chamber width and angle to angle showed similar values among the cohorts. Keratometry measures remained stable despite OSD (CoV lower than 1%).The Tomey CASIA 2 demonstrated reliable repeatability for measuring anterior segment parameters in diverse OSD cohorts. Despite challenges posed by dry eye conditions, this technology holds promise in assessing OSD, suggesting potential clinical protocols similar to those in healthy controls.